Applying laws of propositional logic question: $ \neg \big( p \lor ( \neg p \land q ) \big) \equiv \neg p \land \neg q $

logic

I need to prove that $ \neg \big( p \lor ( \neg p \land q ) \big) $ is logically equivalent to $ \neg p \land \neg q $ using the laws of propositional logic instead of a truth table. I can't figure out which rules work to transform it to $ \neg p \land \neg q $. I am taking a logic course and I want to practice my logical thinking so that I can be ready on test day. This is one I am practicing with and I tried to do De Morgan's, then associativity then idempotence laws, but I don't think this is correct. I also tried to do absorption and then De Morgan's, but I don't think that works either because of the negations and because I need it to be equivalent to $ \neg p \land \neg q $.

Best Answer

Using distibution we have: $$ p \lor ( \neg p \land q ) \equiv \big(p\lor (\neg p)\big)\land \big(p\lor q\big) \equiv 1 \land \big(p\lor q\big) \equiv p\lor q $$ Then De Morgan gives answer